2014
DOI: 10.1371/journal.pone.0102478
|View full text |Cite|
|
Sign up to set email alerts
|

Selection Mosaic Exerted by Specialist and Generalist Herbivores on Chemical and Physical Defense of Datura stramonium

Abstract: Selection exerted by herbivores is a major force driving the evolution of plant defensive characters such as leaf trichomes or secondary metabolites. However, plant defense expression is highly variable among populations and identifying the sources of this variation remains a major challenge. Plant populations are often distributed across broad geographic ranges and are exposed to different herbivore communities, ranging from generalists (that feed on diverse plant species) to specialists (that feed on a restr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
60
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 47 publications
(63 citation statements)
references
References 55 publications
2
60
0
1
Order By: Relevance
“…Climatic variations (Agosta 2006), phenological and physiological state of the plants (Ayabe et al 2014), local selective pressures on plant traits (Castillo et al 2014), or the presence of plant endophytic symbionts and insect pathogens (Crawford et al 2010;Gurulingappa et al 2010) may also have an influence on host plant availability for the insects. Such variability in plant resource may have a significant impact on the spatiotemporal patterns of plant selection for female oviposition.…”
Section: Discussionmentioning
confidence: 99%
“…Climatic variations (Agosta 2006), phenological and physiological state of the plants (Ayabe et al 2014), local selective pressures on plant traits (Castillo et al 2014), or the presence of plant endophytic symbionts and insect pathogens (Crawford et al 2010;Gurulingappa et al 2010) may also have an influence on host plant availability for the insects. Such variability in plant resource may have a significant impact on the spatiotemporal patterns of plant selection for female oviposition.…”
Section: Discussionmentioning
confidence: 99%
“…In the native range, scopolamine was positively selected in three populations. Previous evidence shows that this alkaloid is a component of resistance to herbivores of D. stramonium in its native range, though it does not account for all variation in resistance owing to spatial variation in the pressure exerted by specialist herbivores (see Castillo et al, 2014;Miranda-Pérez et al, 2016). For instance, the dietary specialist leaf beetle Lema trilineata daturaphila and the seed predator Trichobaris soror are absent in tropical, low altitude, locations of central Mexico (Castillo et al, 2014;J.…”
Section: Discussionmentioning
confidence: 99%
“…Alkaloids are toxic to animals, affecting enzymes and altering different physiological processes; some have strong effects on the nervous systems (Mithöfer & Boland, 2012). Studies have shown selection on one or two tropane alkaloids of D. stramonium when consumed by dietary specialist or generalist herbivores (Castillo et al, 2014;Miranda-Pérez et al, 2016;Shonle & Bergelson, 2000).…”
Section: Evidence Of Changes In Defence Between Native and Non-nativementioning
confidence: 99%
See 1 more Smart Citation
“…The secondary plant compound is more effective against herbivores specialist, but the precursor is still effective against generalist. Then, when there is a community of generalists, D. stramonium produces atropine [82].…”
Section: Pure and Applied Biogeographymentioning
confidence: 99%